Structural characterization and phylogenetic relationships of myotoxin II from Atropoides (Bothrops) nummifer snake venom, a Lys49 phospholipase A2 homologue - Angulo Ugalde, Yamileth (2002)
In order to analyze its structure–function relationships, the complete amino acid sequence of myotoxin II from Atropoides (Bothrops) nummifer from Costa Rica was determined. This toxin is a Lys49-type phospholipase A2 (PLA2) homologue, devoid of catalytic activity, structurally belonging to class IIA. In addition to the Asp49 → Lys change in the (inactive) catalytic center, substitutions in the calcium-binding loop suggest that its lack of enzymatic activity is due to the loss of ability to bind Ca2+. The toxin occurs as a homodimer of basic subunits of 121 residues. Its sequence has highest similarity to Lys49 PLA2s from Cerrophidion, Trimeresurus, Bothrops and Agkistrodon species, which form a subfamily of proteins that diverged early from Asp49 PLA2s present in the same species, as shown by phylogenetic analysis. The tertiary structure of the toxin was modeled, based on the coordinates of Cerrophidion godmani myotoxin II. Its exposed C-terminal region 115–129 shows several differences in comparison to the homologous sequences of other Lys49 PLA2s, i.e. from Agkistrodon p. piscivorus and Bothrops asper. Region 115–129 of the latter two proteins has been implicated in myotoxic activity, on the basis of the direct membrane-damaging of their corresponding synthetic peptides. However, peptide 115–129 of A. nummifer myotoxin II did not exert toxicity upon cultured skeletal muscle cells or mature muscle in vivo. Differences in several amino acid residues, either critical for toxicity, or influencing the conformation of free peptide 115–129 from A. nummifer myotoxin II, may account for its lack of direct membrane-damaging properties.